2023
DOI: 10.1111/1749-4877.12774
|View full text |Cite
|
Sign up to set email alerts
|

Antifertility effects of EP‐1 (quinestrol and levonorgestrel) on Pacific rats (Rattus exulans)

Jing LIU,
Feiyun TU,
Ming LIU
et al.

Abstract: Pest rodents pose a serious threat to island biodiversity. Fertility control could be an alternative approach to control the impact of rodents on these islands. In this study, we examined the antifertility effects of EP‐1 baits containing quinestrol (E) and levonorgestrel (P) using a dose of 50 ppm E and P at three different ratios (E:P ratio = 1:2, 1:1, and 2:1) on Pacific rats (Rattus exulans) in the Xisha Islands, Hainan, China. Compared to the control group, all animals in EP‐1 treatment groups showed sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…Research on these steroids for rodent fertility control was pioneered in China by Professor Zhibin Zhang (host of the 1st ICRBM in Beijing) (see recent review by Jacoblinnert et al 2022b) and has led to research on EP-1 in other rodent species in Africa, Indonesia, and South Asia. In this volume, Liu et al (2023a) showed that the effects of EP-1 on the Pacific rat, Rattus exulans, were greatest in males, but that the dose and palatability of food baits containing the steroids require further development before field studies on islands would be feasible. Liu J. et al's results reflect the need to directly assess the response of a species to a control agent that has been tested in several other species (Jacoblinnert et al 2022;Massei et al 2023).…”
Section: Fertility Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on these steroids for rodent fertility control was pioneered in China by Professor Zhibin Zhang (host of the 1st ICRBM in Beijing) (see recent review by Jacoblinnert et al 2022b) and has led to research on EP-1 in other rodent species in Africa, Indonesia, and South Asia. In this volume, Liu et al (2023a) showed that the effects of EP-1 on the Pacific rat, Rattus exulans, were greatest in males, but that the dose and palatability of food baits containing the steroids require further development before field studies on islands would be feasible. Liu J. et al's results reflect the need to directly assess the response of a species to a control agent that has been tested in several other species (Jacoblinnert et al 2022;Massei et al 2023).…”
Section: Fertility Controlmentioning
confidence: 99%
“…In this volume, Liu et al. (2023a) showed that the effects of EP‐1 on the Pacific rat, Rattus exulans , were greatest in males, but that the dose and palatability of food baits containing the steroids require further development before field studies on islands would be feasible. Liu J. et al.’ s results reflect the need to directly assess the response of a species to a control agent that has been tested in several other species (Jacoblinnert et al.…”
Section: Re‐emergence Of Interest In Fertility Controlmentioning
confidence: 99%